Effect of plant density and fertilization on winter rapeseed yield - Drobitko, А. (Scientific Progress & Innovations, 2025)
The aim of this review was to determine the influence of plant density and fertilization on winter rapeseed yield, considering varietal and regional characteristics, to enhance the efficiency of crop cultivation under current economic and climatic conditions. Winter rapeseed is an important crop used in the food industry and for the production of renewable energy sources, necessitating an increase in its yield and cultivation efficiency. The article examines the key factors affecting winter rapeseed productivity: plant density and fertilization systems. It was established that the optimal plant density depends on the region, sowing dates, and growing conditions. According to research, the optimal density for winter rapeseed hybrids is 30–60 plants/m², while for cultivars, it is 80–100 plants/m². Late sowing dates require an increase in plant density by 20–50 %, as underdeveloped crops are more vulnerable to winter conditions. The article also highlights fertilization as another critical factor influencing yield. Winter rapeseed has a high demand for micro- and macronutrients, including nitrogen, phosphorus, potassium, and sulfur. To ensure stable growth and development, optimal application rates are: nitrogen fertilizers at 150–200 kg/ha, phosphorus at 60–90 kg/ha, potassium at 80–120 kg/ha, and sulfur at 20–40 kg/ha. The sensitivity of winter rapeseed to deficiencies in boron, molybdenum, zinc, and other micronutrients, which enhance plant stress resistance, is also noted. The study results indicate that optimizing plant density and fertilization systems can increase winter rapeseed yield by 40–60 % and the oil content in seeds to 50–55 %. Moreover, ensuring optimal density and fertilization parameters reduces cultivation costs by minimizing seed and chemical fertilizer use. The article provides recommendations for seeding rates, fertilization systems, and plant density management, tailored to the regions of Ukraine. The findings are of practical significance for optimizing winter rapeseed cultivation technologies, improving the profitability of production, and enhancing the environmental sustainability of agricultural systems.